Risks related to the presence of Salmonella sp. during rearing of mealworms (Tenebrio molitor) for food or feed: Survival in the substrate and transmission to the larvae. (June 2019) - Wynants, E.; Frooninckx, L.; Van Miert, S.; Geeraerd, A.; Claes, J.; Van Campenhout, L.
Abstract: During rearing of insects for food and feed, their microbial safety is of utmost importance, but little is known on the transmission of food pathogens from the substrate to the insects. The aim of this study was to investigate whether transmission of Salmonella sp. to mealworms ( Tenebrio molitor ) can occur, in case mealworms are fed with contaminated wheat bran as substrate. Three consecutive contamination levels of a mixed culture of three Salmonella enterica strains in wheat bran were studied, being 7, 4, and 2 log cfu/g. At each of these contamination levels, Salmonella sp. remained present in the bran during the experimental period of seven days when larvae were absent. This indicates that Salmonella sp. can survive for at least seven days when wheat bran is stored, as is done in industrial rearing facilities. When larvae were present, however, the survival of Salmonella sp. in larvae and bran depended on the contamination level. When bran was contaminated with 7 log cfu/g Salmonella sp., the bacterium was still present after seven days in both larvae and bran, with average numbers of 3.7–4.1 log cfu/g, respectively. At a contamination level of the bran of 4 log cfu/g, Salmonella sp. counts decreased until <1.5 log cfu/g and <1.0 log cfu/g on average in bran and larvae, respectively. However, the pathogen was still detected in most larvae and bran samples after seven days, as was shown using presence/absence testing. At a contamination level of 2 log cfu/g, presence/absence testing revealed Salmonella sp. to remain present in some bran samples after seven days, but surprisingly was not detected in the larval samples. Apparently, when present at a low level in the substrate, Salmonella sp. is not retained by the larvae during the seven day period, likely either because of competitive exclusion by the endogenous larval microbiota and/or because of antibacterial activity of the larvae. Highlights: Food pathogens may be present in substrates for insects reared for feed and food. Survival of Salmonella in wheat bran and transmission to mealworms was studied. Salmonella survived for at least seven days in the bran when larvae were absent. When larvae were present, Salmonella was reduced in both bran and larvae by day 7. Salmonella presence in larvae at day 7 depended on initial numbers in the bran.